2D Supramolecular networks of dibenzonitrilediacetylene on Ag(111) stabilized by intermolecular hydrogen bonding. Issue 16 (11th April 2017) - Galeotti, G.; Ebrahimi, M.; Lipton-Duffin, J.; MacLeod, J. M.; Rondeau-Gagné, S.; Morin, J.-F.; Rosei, F.
Abstract : Hydrogen bonding controls the intermolecular distances in supramolecular networks – a platform to design molecular patterns at surfaces/interfaces. Abstract : The two-dimensional (2D) surface-directed self-assembly of dibenzonitrile diacetylene (DBDA) on Ag(111) under ultrahigh vacuum (UHV) conditions was investigated by combining scanning tunneling microscopy (STM), X-ray photoelectron spectroscopy (XPS) and theoretical simulations based on density functional theory (DFT) calculations. The molecule consists of two benzonitrile groups (–C6 H4 –CN) on each side of a diacetylene (–CC–CC–) backbone. The terminating nitrile (–CN) groups at the meta position of the phenyl rings lead to cis and trans stereoisomers. The trans isomer is prochiral and can adsorb in the R or S configuration, leading to the formation of enantiomeric self-assembled networks on the surface. We identify two simultaneously present supramolecular networks, termed parallel and chevron phases, as well as a less frequently observed butterfly phase. These networks are formed from pure R (or S ) domains, racemic mixtures ( RS ), and cis isomers, respectively. Our complementary data illustrates that the formation of the 2D supramolecular networks is driven by intermolecular hydrogen bonding between nitrile and phenyl groups (–CN⋯H–C6 H3 ). This study illustrates that the molecular arrangement of each network depends on the geometry of the isomers. The orientation of the nitrile group controls the formation of the most energetically stable network via intermolecular hydrogen bonding.